Pultrusion and compression moulding of thermoplastic pre-impregnated materials reinforced by continuous glass fibres - Novo, J. P. (2019)
Four different pre-impregnated materials were used in this study: towpregs and tapes (PCT´s), both produced in our manufacturing lines and commingled fibres (TWINTEX®)) and tapes (CompTape®) supplied by external companies. The laboratory made pre-impregnated materials consisted of carbon and glass fibres and a polypropylene thermoplastic matrix. Pultrusion and heated compression moulding processes were used to obtain composite profiles and plates and were described in this paper. The optimization of those processes was made by studying the influence of the most relevant processing parameters – preheating, heating and cooling inside the die and speed for the pultrusion, and heating temperature, pressure and time for compression moulding - in the final properties of the produced carbon and glass fibres thermoplastic matrix pre-impregnated materials and composites. One interesting target to be achieved was the increase of pultrusion speeds to meet the industrial needs. This was possible particularly with the thermoplastic composite Tape due to its consistency. The composite relevant mechanical properties were determined and the final composites had optical microscopy and calcination tests.